VERSÕES E INSERÇÕES DO SERVIÇO DE PSICOLOGIA NA ESCOLA A PARTIR DA PERSPECTIVA DA PSICOLOGIA HISTÓRICO-CULTURAL - Ariane Meneghetti de Freitas (2022)
ABSTRACT In December 2019, Law No. 13935/2019 was approved, which deals with the provision of psychology and social work services in public basic education networks, which aims to meet the needs and priorities defined by education policies through multidisciplinary teams of psychology services. In view of this, the interest in the insertion of the psychologist in the school context has increased. The present work had as its general objective to analyze the conceptions of teachers about the insertion of the psychologist in the school institution, based on the Cultural-Historical Psychology (CHPs). From these bases, it was presented the articulation between Cultural-Historical Psychology, Educational/School Psychology and the insertion of the psychologist in the educational institution. In the search for answers to understand how teachers understand this insertion, we conducted questionnaires and semi-structured interviews with teachers from two state schools in Campo Grande - MS, one of them being part of the Young Learner Advancement Project (AJA), a project which has a psychologist in the multidisciplinary team. In the analysis of the questionnaires, we verified that the teachers, participants of the research, are overloaded with work and believe that the psychologist has the responsibility of taking that overload away from them, especially in relation to student behavior and conflicts existing in the school context. The teachers, in most of the answers, do not know or do not understand what a school psychologist does and what their attributions should be within the school context. Their reports are based on the perspective of pathologizing and medicalizing the students. Thus, the importance and necessity of the psychologist included in the pedagogical team is evidenced, contributing to the construction of educational proposals aligned to the principles of Inclusive Education. Keywords: School Psychologist. Senses and meanings of the Teacher. Cultural-Historical Psychology.